Can Carbon Labeling Be Development Friendly? - Brenton, Paul; Edwards-Jones, Gareth; Jensen, Michael F. (World Bank, Washington, DC, 2012)
Carbon accounting and labeling for products are new instruments of supply chain management that may affect developing country export opportunities. Most instruments in use today are private business management tools, although the underlying science and methodologies may spread to issues subject to public regulation. This note seeks to inform stakeholders involved in the design of carbon labeling schemes and in the making of carbon emission measurement methodologies about an overlooked issue: how can carbon labeling are made to be both developments friendly and scientifically correct in its representation of developing-country agricultural sectors? As a result of the pressures placed on designers and users of carbon accounting and labeling instruments, there is a risk that carbon accounting and labeling instruments will not properly represent the complexity of production systems in developing countries.